The Role Of Nagari-Owned Enterprises In Creating Intreprenuship Among The Younger Generation In Nagari Pilubang - Mahzuardi; M.Giatman; Yuliana (Institute of Computer Science (IOCS), 2022)
Nagari village-owned enterprise is a business entity that aims to explore the potential that exits in the village, both natural resources and human resources. However, what happens is that the role of bumnag cikal kelapa nagari pikapal has not been able to encourage improvements in creating entrepreneurship for the younger generation and improving people’s welfare, it is still far from expectations, so it has a huge impact on the progress of bumnag cikal kelapa to develop. To establish bumnag, it is necessary to conduct in-depth studies, what potential can be explored in the area, so that it can compete with the same business. And what needs to be noted is that the spirit of the establishment of bumnag should be based on the entrepreneurial social aspect, which means the balance of socially based business aspects.